AN UNUSUAL CASE OF BLOODY TEARS - Awan, Sarah; Kazmi, Hasan Sajid; Awan, Abdul Aziz (Journal of Ayub Medical College Abbottabad, 2006)
Conjunctival bleeding is usually caused by non accidental or accidental conjunctival laceration, conjunctival tumors and nasolacrimal sac tumors. We report here a rare case of conjunctival bleeding which was self induced using cinnamon bark. Keywords: Bloody Tears, Conjunctiva, Eye